2022
DOI: 10.3390/biomedicines10030550
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome in Non-Alcoholic Fatty Liver Disease: From Mechanisms to Therapeutic Role

Abstract: Non-alcoholic fatty liver disease (NAFLD) is considered to be a significant health threat globally, and has attracted growing concern in the research field of liver diseases. NAFLD comprises multifarious fatty degenerative disorders in the liver, including simple steatosis, steatohepatitis and fibrosis. The fundamental pathophysiology of NAFLD is complex and multifactor-driven. In addition to viruses, metabolic syndrome and alcohol, evidence has recently indicated that the microbiome is related to the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 188 publications
1
21
0
Order By: Relevance
“…There are more than 100 trillion microorganisms in the human gut (about 1.5 kg total weight), making it one of the most diverse ecosystems ( 48 ). It has been reported that camel milk can regulate the intestinal flora structure of mice with colitis, reduce the inflammatory response in mice, and reduce colitis in mice ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are more than 100 trillion microorganisms in the human gut (about 1.5 kg total weight), making it one of the most diverse ecosystems ( 48 ). It has been reported that camel milk can regulate the intestinal flora structure of mice with colitis, reduce the inflammatory response in mice, and reduce colitis in mice ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…While there are a variety of microbiome signatures implicated in NAFLD/NASH, the data are relatively immature, and firm conclusions are necessarily difficult due to potential heterogeneity in studied population ages, geographies, and diets, as well as the actual tools used to sequence the microbiome [ 114 ]. Different microbiotal signatures may predispose to NAFLD and liver fibrosis through multiple different pathways which are beyond the scope of this review, though are well-described in Aron-Wisnewsky et al [ 114 ] and Gupta et al [ 115 ]. However, one microbiotal constituent consistently implicated is lipopolysaccharide (LPS), a Gram-negative bacteria cell wall component, which has been recently linked to multiple metabolic diseases including atherosclerosis and T2DM as well as NAFLD [ 113 , 116 ].…”
Section: Bodymentioning
confidence: 99%
“…In the last decades, fecal transplantation experiments in mice have provided a growing body of evidence about a causal role between GM alterations and NAFLD/NASH development [ 71 , 72 ]. GM was studied in various animal models of NAFLD, and its alteration was found to be associated with NAFLD genesis and progression.…”
Section: Gut Microbiota and Nafld Development In Animal Modelsmentioning
confidence: 99%
“…Several hypotheses have been formulated as to how the GM may contribute to NAFLD development and progression into NASH. As previously mentioned, they include increased intestinal permeability, leading to an increased absorption by the host of microbially produced toxins and metabolites, such as LPS, trimethylamine N-oxide (TMAO), choline, and ethanol, which trigger inflammation and affect immunity [ 71 ]. Infiltrating immune cells such as monocyte-derived macrophages and neutrophil granulocytes, two mediators of the hepatic inflammation during NASH, seem to have a relevant role in the microbiota-mediated worsening of NAFLD; in fact, chemokine receptor antagonists, by inhibiting monocyte recruitment, reduce hepatocyte ballooning, fibrosis, and inflammation in both the Western diet and the MCD diet models [ 87 ].…”
Section: Gut Microbiota and Nafld Development In Animal Modelsmentioning
confidence: 99%